Moodle Virtual Class Effectivity toward Cadets’ Learning Motivation and Speaking Ability - Yudhanita Pertiwi; Ningrum Astriawati; Waris Wibowo; Lukas Kristianto (Universitas Cokroaminoto Palopo, 2021)
This research aimed at identifying the effectivity of applying Moodle virtual class on cadets’ learning motivation and cadets’ motivation in speaking ability in the pandemic of Covid-19. Moodle is one of open source of e-learning software used in lecturing process. The research sample was Studi Nautika Cadets of Sekolah Tinggi Maritim Yogyakarta who were taking Maritime English II class. This research is a descriptive quantitative research. It employed online questionnaire as data collecting method. This study resulted that Moodle usage achievement effectivity on cadets’ learning motivation in Maritime English II subject gained 80.83% agreement. Furthermore, it the effectivity of using Moodle in Maritime English II resulted in 90.63% in Cadets’ motivation in speaking.